Human dental pulp stem cells can differentiate into Schwann cells and promote and guide neurite outgrowth in an aligned tissue‐engineered collagen construct in vitro. Issue 4 (18th December 2013) - Martens, Wendy; Sanen, Kathleen; Georgiou, Melanie; Struys, Tom; Bronckaers, Annelies; Ameloot, Marcel; Phillips, James; Lambrichts, Ivo
Abstract : In the present study, we evaluated the differentiation potential of human dental pulp stem cells (hDPSCs) toward Schwann cells, together with their functional capacity with regard to myelination and support of neurite outgrowth in vitro . Successful Schwann cell differentiation was confirmed at the morphological and ultrastructural level by transmission electron microscopy. Furthermore, compared to undifferentiated hDPSCs, immunocytochemistry and ELISA tests revealed increased glial marker expression and neurotrophic factor secretion of differentiated hDPSCs (d‐hDPSCs), which promoted survival and neurite outgrowth in 2‐dimensional dorsal root ganglia cultures. In addition, neurites were myelinated by d‐hDPSCs in a 3‐dimensional collagen type I hydrogel neural tissue construct. This engineered construct contained aligned columns of d‐hDPSCs that supported and guided neurite outgrowth. Taken together, these findings provide the first evidence that hDPSCs are able to undergo Schwann cell differentiation and support neural outgrowth in vitro, proposing them to be good candidates for cell‐based therapies as treatment for peripheral nerve injury.—Martens, W., Sanen, K., Georgiou, M., Struys, T., Bronckaers, A., Ameloot, M., Phillips, J., Lambrichts, I. Human dental pulp stem cells can differentiate into Schwann cells and promote and guide neurite outgrowth in an aligned tissue‐engineered collagen construct in vitro . FASEB J. 28, 1634–1643 (2014). www.fasebj.org